DEVELOPMENT OF TOOLS OF THE X-RAY COLLIMATOR (DEV-X) - Prasetya, I Made Lana; Santoso, Hari; Wibowo, Gatot Murti (Postgraduate Program , Poltekkes Kemenkes Semarang, 2020)
Background: Technological developments, especially in the field of radiology, is growing rapidly. The radiology quality assurance system has also developed, one of which is the Collimator Test Tools. The method of testing x-ray beams using this tool has also been developed, such as using film and using IP. However, the development of this method has a drawback, namely that the examiner is required to have special skills in image post-processing. The development of Collimator Test Tools by utilizing the nature of x-rays which causes certain substances such as calcium tungstate or zinc sulfide to glow light (luminance) has been done a lot, but there is no study of these products. Therefore, the researcher wants to develop a product by designing a Collimator test tool based on digital image analysis technology (Dev-X) and a digital camera with Android-based calculations on a wirelessly connected smartphone as an update of the testing method. Objective: To create a collimator test tool for x-ray machines based on digital image analysis technology (Dev-X). Methods: This is a research experiment with a posttest group only design type. Research Location at the Radiology Laboratory of the Radiodiagnostic and Radiotherapy Engineering Academy (ATRO) Bali. Result: Functional Test of Dev-X Products (hardware and software), all components function properly. However, it cannot be assessed significantly from statistical results. Conclusion: The creation and proper functioning of hardware and software tools collimator test tool Dev-Xon android smartphone and show the calculation results of the x-ray beam automatically.Â Â Â